2012
DOI: 10.1007/s00256-012-1503-5
|View full text |Cite
|
Sign up to set email alerts
|

Visual expertise in detecting and diagnosing skeletal fractures

Abstract: The results suggest that the performance advantage of expert radiologists is underpinned by superior pattern recognition skills, as evidenced by a quicker time to first fixate the pathology, and less time spent searching the image.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 14 publications
5
61
1
Order By: Relevance
“…In general visual search time decreases with increasing levels of expertise (Krupinski 1996; Manning et al 2006; Alzubaidi et al 2009; Cooper et al 2010; Kok et al 2012, 2016; Voisin et al 2013; Wood et al 2013; Giovinco et al 2014; Rubin et al 2015). The average time experts took to view an image varied largely between studies, ranging from 4 s up to around 45 s, due to differences in task characteristics (detection, interpretation or both; lesion subtlety) and time limits.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general visual search time decreases with increasing levels of expertise (Krupinski 1996; Manning et al 2006; Alzubaidi et al 2009; Cooper et al 2010; Kok et al 2012, 2016; Voisin et al 2013; Wood et al 2013; Giovinco et al 2014; Rubin et al 2015). The average time experts took to view an image varied largely between studies, ranging from 4 s up to around 45 s, due to differences in task characteristics (detection, interpretation or both; lesion subtlety) and time limits.…”
Section: Resultsmentioning
confidence: 99%
“…Despite these differences, there are some consistent patterns in how experts move their eyes compared to less proficient observers: experts fixate faster on an abnormality (Krupinski 1996; Nodine et al 1996; Kundel et al 2007; Cooper et al 2010; Wood et al 2013; Mallett et al 2014) and make more fixations (Manning et al 2006; Alzubaidi et al 2009; Voisin et al 2013; Giovinco et al 2014). Experts or subspecialized experts tended to fixate on an abnormality within 0.5–2 s in mammography and CT studies, around 3 s in skeletal and chest X-rays, and up to 5 s in subtle fracture cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact it is reported that students for some tasks can use up to twice as long time as experts (14). The question, however, why the most experienced radiographers (Group 3) in our study used at least as long time as the students did is open to discussion.…”
Section: Sidementioning
confidence: 64%
“…Most of the research on the perceptual and cognitive processes that underlay the diagnostic imaging processes have been from the point of view of the diagnostic decision-maker, and less from the point of the radiographer or radiology technologist (8)(9)(10). Admittedly, there are several studies where radiographers themselves act as diagnostic reporters, in for instance CT imaging (11) and conventional (planar/ skeletal/ projected) X-ray imaging (12)(13)(14)(15), but these are other types of imaging tasks than accepting/ rejecting.…”
Section: Introductionmentioning
confidence: 99%